Kapitalisme Dalam Perspektif Ekonomi Politik dan Ekonomi Islam - Isra Ruddin; Udi Rusadi (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
A discussion of the modern economic system, usually refers to two major systems, namely capitalism based on the capital markets (capital) and guided socialism which tried to solve problems of production, consumption and distribution through the chain of command. In addition to these two major systems, also known as the Islamic economic system, which refers to the economic practice of the Prophet Muhammad, peace be upon him. Islamic economic system is an alternative to the fundamental problems of the two major systems that already exist. However, when referring to the conditions of the birth of Islam in the midst of Arab society steeped in culture trade, alleged the influence of the capitalist culture of the economic system of Islam, so Islam is perceived closer to capitalism than socialism. Through the study of literary conclusion that Islam and capitalists are the two things affect each other. Sociologically, Islam is present in a capitalist society that both have an attachment. Capitalism, especially trade capitalism existed before Islam came. Before the birth of Islam, Mecca has become the center of international trade and finance. The Prophet Muhammad himself was a merchant before it became a prophet. Thus, capitalism is an ideology or a system that comes from the outside and into the schools of economic thought incoming and economic influence of Islam, although Islam also influence and correct the economic life or Capitalism applicable. Therefore Islam and capitalism are two forces that interact and influence. Keywords: Capitalism, Political Economy, Islamic Economics.